Analisis Kondisi Fisik Atlet Putra Floorball Universitas Negeri Surabaya - Ekarina kamanita br meliala (Journal of Sport Science and Education, 2019)
Problems in this research is the physical condition of Floorball men athlete of University of Surabaya who have not won for the last few years. The purpose of this research is to determinethe physical condition of Floorball menathlete of University of Surabaya with a research subject of 15 people. The tipe of research used is quantitative with descriptive method. Based on data processing and analysis, (1) the results are the running speed of men athleteof University of Surabaya is included in the good category with 60% precentage. (2) The abdominal muscle strength included in the good category with 66,7% (3) The arm muscle strength included into poor category with 73.3%. (4) The balance included into medium category with 66,7% (5) The endurance included into medium category with 66,7% (6) The agility included into medium category with 66,7%. The conclusion of this research indicates that the physical condition of Floorball menathlete of University of Surabaya is still in the medium category,especially in the arm muscle strengths test included into poor category, so that requires intensive training to improve the physical condition better.